The relationship between insomnia and trait anger and anger expression among adolescents - ERGÜN, AYŞE; ŞİŞMAN, FATMA NEVİN (WILEY, 2021)
Problem: Sleeplessness and inadequate sleep may cause an adolescent to experience reduced self-control and behavioral problems that include anger and an inclination toward crime. This study aimed to examine the relationship between insomnia and trait anger and anger expression among adolescents. Methods: The study was conducted with 749 students from 27 high schools who were selected by using the stratified cluster sampling method. The data were collected with an Individual Characteristics Form, the Trait Anger/Anger Expression Inventory, and the Insomnia Severity Index. Findings: The insomnia scores of 14.0% of the participants were over the clinical insomnia threshold of 15 points. A positive relationship was found between insomnia and trait anger, anger-in, anger-out scores but a negative relationship with anger control scores. It was observed that the determinants of the severity of insomnia were trait anger and anger-in, dozing off in class, feeling anger after a sleepless night, sleeping <6 h a night during the week and over the weekend. Conclusion: It was found that 14.0% of the participants experienced insomnia and there was a two-way correlation between insomnia and anger among adolescents.
Keywords: aggression; health behavior; quality of life; violence; SHORT-SLEEP DURATION; EMOTION REGULATION; DEPRIVATION; ASSOCIATION; RUMINATION; PATTERNS; STUDENTS; SCHOOL